Magnetic Properties and Core Loss Behavior of Fe-6.5wt.%Si Ribbons Prepared by Melt Spinning. (26th January 2015) - Wang, S.; Jiang, Y. M.; Liang, Y. F.; Ye, F.; Lin, J. P.
Abstract : Fe-6.5wt.%Si alloy is prepared in the form of continuous ribbons with 25 mm in width and 0.03 mm in thickness by using melt spinning technique. The ribbons are flexible and could be wounded into tapes. DC magnetic properties and core loss behaviors of the ribbons after heat treatment are investigated in this paper. The magnetic properties are compared with ribbons by cold rolling and CVD methods. The melt spinning ribbons exhibit much less core loss in the frequencies more than 10 kHz. The melt spinning ribbons are promising to be used for electric devices used in medium or higher frequencies.